The Urgency of Availability of Facilities, Time, and Parental Guidance for Students’ English Learning Achievement - Riryn Fatmawaty; Syafi’ul Anam (Jurnal PTK dan Pendidikan, 2022)
Abstract: The objective of this research was to determine the urgency of availability of facilities, time, and parental guidance at home for students' English learning achievement. For that, this research needs to explore the correlation between the things. Therefore, we used a correlational method with 118 English language education program students as participants or subjects for doing research. Students need the motivation from their parents, not only teachers at school. This argument is based on the consideration that children spend more time with their parents at home. Data collection was carried out using documentation and questionnaires. We used SPSS 25 to calculate and answer the hypotheses of each variable. Then used F statistics and multicorrelation to answer the hypotheses of all variables. Based on the results of the study, F change 0.001 <0.05 This means that the hypothesis is accepted and there is a significant relationship between study time learning facilities and parental guidance on student achievement. So that, it can be concluded that each unit increases learning indicators such as; learning facilities, study time and also parental support accompanied by changes in student achievement units in English.Keywords: Learning Facilities; Learning Time; Parental Guidance; Learning Achievement.